2020
DOI: 10.2147/ppa.s258999
|View full text |Cite
|
Sign up to set email alerts
|

<p>Psychosocial Predictors of Self-Efficacy Related to Self-Reported Adherence in Older Chronic Patients Dealing with Hypertension: A European Study</p>

Abstract: Non-adherence to clinical prescriptions is widely recognized as the most common cause of uncontrolled hypertension, contributing to develop acute and chronic cardiovascular diseases. Specifically, patients' unintentional non-adherence is related to psychosocial factors as beliefs about medications, perceived physician's communication effectiveness and medication-specific social support. The aim of this study was to observe the impact of these factors on self-efficacy in relation to pharmacological and non-phar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…Nonadherence to treatment is the most common cause of treatment failure. Research has identified multiple factors with an impact on adherence and self-care [6,[10][11][12][13][14]. The WHO has defined five groups of factors contributing to non-adherence: (1) patient and familydependent factors, (2) illness-related factors, (3) treatment-related factors, (4) healthcare system-related factors, and (5) socio-demographic and economic factors [15].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nonadherence to treatment is the most common cause of treatment failure. Research has identified multiple factors with an impact on adherence and self-care [6,[10][11][12][13][14]. The WHO has defined five groups of factors contributing to non-adherence: (1) patient and familydependent factors, (2) illness-related factors, (3) treatment-related factors, (4) healthcare system-related factors, and (5) socio-demographic and economic factors [15].…”
mentioning
confidence: 99%
“…The available data [14,[22][23][24][25], which come mainly from the US, document the role of communication in the physician-patient relationship. Few European reports are available [14,25], and to the best of our knowledge, there have been no Polish studies focusing on the relationship between communication and adherence or self-care in patients with HT.…”
mentioning
confidence: 99%
“…However, the role of belief is influenced by the existence of positive belief in treatment with a value (β=0.13 p <0.001). 27,28 Finding 5: Social support Social support and self-efficacy were found to be significant for physical activity with a value of p <0.01, = 0.45) and social support p<0.01, (β=0.05, p<0.001). 23 This concurs with the results of Hu's research which revealed that support Social family had a relationship with medication adherence and blood pressure measurement with an odds ratio (OR) of 1.39 (95% confidence interval (CI) 1.03-1.87), odds ratio (OR) 1.33 (95% confidence interval (CI) (1.02-1.74).…”
Section: Finding 4: Positive Beliefs About Treatmentmentioning
confidence: 97%
“…Non-adherence to treatment was the cause of uncontrolled hypertension with a score (β=-0.02, p=0.031). 28 Nine studies did not mention that there was intentional non-adherence to factors affecting selfefficacy in hypertension treatment. 21,[23][24][25][26][27]29,30…”
Section: Finding 1: Intentional Non-compliancementioning
confidence: 99%
See 1 more Smart Citation